Seasonality and Annual Utilization Patterns of Antibacterials at Muhimbili National Hospital, Dar es Salaam, Tanzania: A 2015 Monthly Survey - Sangeda, Raphael Zozimus; Urassa, Mariki I.; Buma, Deus; Musiba, George Nyamanda; Chiwanga, Faraja S.; Chambuso, Mhina; Horumpende, Pius Gerald (Frontiers in Tropical Diseases, 2022)
Introduction Antibacterial utilization studies can help identify areas of intervention of antimicrobial stewardship programs (ASP) to facilitate rational use and prevent the emergence of antimicrobial resistance (AMR). Assessment and comparison of antibacterial utilization depend on the Anatomical Therapeutic Chemical (ATC) classification system and Defined Daily Dose (DDD) recommended by the World Health Organization (WHO) collaborative center for international drug monitoring. This study aimed to determine the DDD of each prescribed antibacterial group and the proportions of wide-spectrum antibacterials used at Muhimbili National Hospital (MNH) in Tanzania to allow baseline data for hospital ASPs. Methods A retrospective analytical study using data collected from 1st January 2015 to 31st December 2015 was undertaken at MNH. Data on antibacterials prescribed and dispensed were obtained from the MNH database. The ATC/DDD system was used to classify and quantify the antibacterial utilization patterns. Results A total of 10,643.1 DDDs were used in thirteen ward units at the Kibasila, Mwaisela and Sewahaji blocks of the MNH. Eighteen different antibacterials were prescribed and dispensed to 1496 patients. Capsules were the most dispensed dosage form. The drug ciprofloxacin was the leading antibacterial prescribed, with a DDD of about 3780 (35.5%) per year. This was followed by metronidazole and amoxicillin. The proportion of wide-spectrum antibacterials was as high as 66%. Utilization peaks were noted in April, July and September. There was a significant monthly increase in antibacterials utilization between January and December 2015 (p-value = 0.002, R-square = 0.64). The trends forecasted increased through June 2016. Conclusions Utilization trends indicated a significant monthly increase in 2015 at MNH wards in Tanzania. The use of wide-spectrum antibacterials was widespread. This calls for continued antibacterial utilization surveillance and implementation of hospital-based ASP to mitigate the rapidly rising global threat of AMR.